FACTORS INFLUENCING CONTRACEPTIVE UTILIZATION IN POSTPARTUM IN MOTHER AND CHILD HOSPITAL SITI FATIMAH MAKASSAR (Nusantara Medical Science Journal, 2018)
Introduction : Postpartum contraception is defined as utilization of contraceptive within 42 days after a labor to prevent close interval of pregnancy. After a live birth, WHO recommended interval before attempting the next pregnancy is at least 24 months in order to reduce the risk of adverse maternal, perinatal, and infant outcomes. Several factors influence maternal in utilizing contraception after giving birth. Objective : To recognize factors influencing contraception utilization in postpartum period in Mother and Child Hospital Siti Fatimah Makassar. Study Method : The study was observational analytic study with cross sectional method. Seventy respondents were obtained with consecutive sampling technique. Chi square test was used to determine linkage value. Result : The result showed that factors affecting contraception utilization in postpartum period in Mother and Child Hospital Siti Fatimah Makassar were knowledge about contraception (p value 0.000, OR = 24.5 (2.995 – 200.437)), number of children (p value 0.004, OR = 4.182 (1.541 – 11.347)), education (p value 0.002, OR = 4.915 (1.770 – 13.646)), and husband encouragement (p value 0,000 ,OR=6,240 (2,211-17,608)). Resources variable was not related to this study. The most affecting variable was knowledge about contraception. Conclusion : Factors influecing contraception utilization in postpartum period were knowledge about contraception, number of children, education, and husband encouragement. The most affecting factor was knowledge about contraception. The most affecting factor is knowledge about contraception.
Keywords: Postpartum contraception.